Electrochemical and analytical techniques for sustainable corrosion monitoring : advances, challenges and opportunities - Aslam, Jeenat; Verma, Chandrabhan; Hussain, Chaudhery Mustansar (Elsevier, 2023)
Electrochemical and Analytical Techniques for Sustainable Corrosion Monitoring presents established research and technology for corrosion monitoring and measurements. Corrosion reduction can be controlled via various ways, including process control, cathodic protection, metal impurity reduction, application of surface treatment methods, and incorporation of appropriate alloys. This is the first book that collectively describes corrosion inhibition measurements using chemical, electrochemical, and analytical methods. The book presents state-of-the art techniques for corrosion monitoring by providing detailed studies and testing methods. It also covers the most advanced, industry-oriented challenges for sustainable corrosion monitoring and measurements. The book is a valuable resource for scholars in academia, materials science and applied engineering and chemistry students, and corrosion engineers.